Music for life's sake; education through music in industrially developing societies: priorities and policies - Moore, S. (CESO HagueNL, 1983)
Suggests that music and the arts are the means for tuning into the world. In traditional societies education through the arts is a lifelong process of cultural awareness and socialization. However the survival of these processes is threatened by political, economic and cultural domination, resulting from colonialism, from the modern technological, post industrial and information revolutions, and from the negative effects of the transnational media.